Aromanian Zoonymica from Kleisoura (prefecture of Kastoria) - Siokis, Nikolaos Dimokratous (Zeitschrift für Balkanologie, 2007)
The mountain-village of Kleisoura in the district of Kastoria (Greece) is inhabited by Aromanians, speaking today Aromanian and Greek. Especially the older population has preserved good knowledge of the Aromanian which has strong linguistic relations with the Aromanian of Nymfaio and Kruševo. The dialect is quite uninvestigated, as in generally the interest for Aromanian in Greece is very little. The contribution contains linguistic material from field research in the author’s home village concerning the animal’s denominations, made mainly with stock-breeders and local hunters. The questionnaire consists of 179 Greek words and was answered in Aromanian. The most accepted etymology of the words is added by the author. The collection of animal’s denominations presents unique interest as much as the peculiarity of their origin is concerned as also for the linguistic material that it offers. Characteristic are the predominance of words with Latin origin and the adopting of words from the neighbouring languages Greek, Slav, Turkish, and Albanian.